Romantic codes in the novels written by Miodrag Bulatović - Bečanović, Tatjana (Poznańskie Studia Slawistyczne, 2011)
The paper identifies the romantic codes that are activated in the organization of the novels of Miodrag Bulatovic, relying on the theoretical assumptions of Aleksandar Flaker about the stylistic formation of romanticism, whose postulates occur even outside the periods, mainly as peripheral poetic codes within different systems. The disintegrative energy of this period and its preference for the destruction of the canon came to full expression in the narrative process of Miodrag Bulatovic. Romanticism as a supra-historical and anthropological category is generally based on the maximal postulates that involve the destruction of the existing world, as well as an aggressive attitude towards reality, which is built into the writer’s universe and reaches its climax in his last novel, entitled Gullo Gullo and his eschatological mythemes. The irrational and fantastic images in the narrative process have been equated with real events co-existing as a narrative element completely equal to reality, and what is fantastic, unnatural and unusual reveals itself as very ordinary and realistic, erasing the boundaries between reality and fiction, belonging to one and the same, a diabolical universe, which substantially regulates romantic codes.